Tin atom-containing asymmetric donor material as well as preparation method and application thereof

By designing asymmetric donor materials containing tin atoms and introducing fluorine or chlorine atoms, the photoelectric properties of organic photoelectric materials are optimized, and the synthesis difficulty and cost problems caused by the introduction of tin atoms are solved, thus achieving more efficient photovoltaic performance and a more economical synthesis process.

CN119528967APending Publication Date: 2025-02-28JIANGHAN UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411716244.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

When designing organic photoelectric materials, although the introduction of tin (Sn) atoms can improve material performance, it may lead to increased synthesis difficulties, increased cost, and environmentally friendly problems, and it is difficult to optimize photoelectric characteristics.

Method used

An asymmetric donor material containing tin atoms was designed, with fluorine or chlorine atoms introduced into the structure to optimize the photoelectric properties of the material. Small molecule donor materials with excellent properties are prepared by the synthetic method of specific steps, including multi-step reaction and treatment under specific conditions.

Benefits of technology

Better photovoltaic performance in organic solar cells is achieved, including improved photoelectric conversion efficiency, faster charge mobility and more appropriate energy level differences, ensuring the improvement of material performance while ensuring the feasibility and economicality of synthesis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528967A_ABST
    Figure CN119528967A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field, in particular to an asymmetric donor material containing tin atoms and a preparation method and application of the asymmetric donor material, the structural formula of the asymmetric donor material is shown in the formula 1, and in the structural formula # imgabs0,-X is a fluorine atom or a chlorine atom; the tin atom-containing small molecule donor material designed by the invention can form a proper energy level difference with an acceptor material L8-BO, which is beneficial to exciton dissociation, and has better photovoltaic performance in the test of organic solar cells, and the small molecule has a clear molecular structure in the full-small molecule organic solar cells, so that the application range of the small molecule donor material is widened, and the application range of the small molecule donor material is widened. And the difference between the material and the device batch is very small, so that the method has unique advantages in the commercialization aspect. The method is of great significance for constructing a high-efficiency organic solar cell system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of organic photoelectric materials, in particular to an asymmetric donor material containing tin atoms and a preparation method and application thereof. Background Art

[0002] Tin (Sn), as a metallic element, may be used in the synthesis of semiconductor materials or as a catalyst in the preparation of batteries in some cases, especially in the research of inorganic solar cells or perovskite solar cells. For example, tin-based perovskite materials have become a research hotspot to replace lead-based perovskites due to their potential cost-effectiveness and environmental friendliness.

[0003] Considering the direct introduction of tin atoms into the donor materials of organic solar cells belongs to the category of new material design, which aims to optimize the optoelectronic properties of donor materials by element doping or chemical modification. In the design of organic optoelectronic materials, tin (Sn) plays an important role in improving material performance and expanding its functions due to its unique electronic properties. Such organic small molecule donor materials have excellent performance, however, the introduction of tin (Sn) atoms also has its challenges, such as increased synthesis difficulty, increased cost and environmental friendliness. Therefore, these factors need to be weighed when designing organic optoelectronic materials. At the same time, when constructing organic optoelectronic materials, molecular structures containing F and Cl groups are designed in order to obtain ideal optoelectronic properties, stability and good processing properties, which can enhance the electron affinity of the molecule and reduce the highest occupied orbital (HOMO) energy level or increase the lowest unoccupied orbital (LUMO) energy level, thereby affecting the band structure of the material. This is crucial for the transport of electrons and holes in organic semiconductor materials such as organic photovoltaic cells and organic light-emitting diodes (OLEDs), and can optimize carrier injection, transport and recombination efficiency. Summary of the invention

[0004] The purpose of the present application is to provide an asymmetric donor material containing tin atoms and a preparation method and application thereof, so as to optimize the photoelectric properties of the material and meet the needs of specific applications.

[0005] The present application embodiment provides an asymmetric donor material containing tin atoms, the structural formula of which is shown in Formula 1:

[0006]

[0007] In the structural formula, -X is a fluorine atom or a chlorine atom.

[0008] A method for preparing an asymmetric donor material containing tin atoms, the specific steps are as follows:

[0009] Step 1: Using tetrahydrofuran as solvent and iodine as initiator, magnesium powder and 4-bromo-1,2-difluorobenzene are added, and the mixture is refluxed at 70° C. for 4 h until magnesium is completely consumed, and naturally cooled to room temperature to obtain Grignard reagent 1. Grignard reagent 1 is added dropwise to a toluene solution of benzo[1,2-b:4,5-b']dithiophene-4,8-dione, and stirred at room temperature. At the same time, using tetrahydrofuran as solvent and iodine as initiator, magnesium powder and 5-bromo-3-chloro-2-(2-hexyldiethyl)thiocine are added, and the mixture is refluxed at 70° C. for 2 h until magnesium is completely consumed, and naturally cooled to room temperature to obtain Grignard reagent 2. The newly prepared Grignard reagent 2 is then transferred to a dropping funnel and slowly added dropwise to the mixed solution to which Grignard reagent 1 is added. Subsequently, the mixture is stirred at room temperature overnight, and then tin (II) chloride dihydrate dissolved in 10% HCl is added at room temperature, and the resulting solution is stirred at 50° C. for 3 hours. After completion, the reaction mixture was naturally cooled to room temperature and poured into water to obtain compound (1);

[0010] Step 2: under the protection of argon, n-butyl lithium solution is added dropwise to a tetrahydrofuran solution containing compound (1) at -78°C. After the addition is complete, the mixture is stirred at -78°C for 1 hour, and then compound (1) is added. The mixture is stirred at -78°C for 1 hour, and the temperature is naturally raised to room temperature for reaction for 12 hours. Subsequently, the mixture is cooled to room temperature, a tin reagent solution is added, and then the mixture is stirred at 50°C for another 3 hours to generate compound (2);

[0011] Step 3: Under argon protection, using tetrakis(triphenylphosphine)palladium as a catalyst and toluene as a solvent, the compound (2) obtained in step 2 and 5"-bromo-3',3"-dihexyl-[2,2':5',2"-terthiophene]-5-carbaldehyde are refluxed at 110°C for 8-10h to undergo Stille coupling reaction to obtain compound (3);

[0012] Step 4: Under argon protection, compound (3), 3-hexylrhodanine and a base are added to chloroform solvent, and Knoevenagel condensation reaction is carried out at 60° C. to connect the rhodanine end groups to obtain an organic small molecule donor material containing an asymmetric two-dimensional side chain.

[0013] Furthermore, in the step 1, the molar ratio of 5-bromo-3-chloro-2-(2-hexyldiethyl) thiocine, 4-bromo-1,2-difluorobenzene and benzo[1,2-b:4,5-b']dithiophene-4,8-dione is 1:2:5; and the molar ratio of benzo[1,2-b:4,5-b']dithiophene-4,8-dione to the tin reagent is 1:5.

[0014] Furthermore, the tin reagent solution in step 2 is prepared by dissolving tin (II) chloride dihydrate in 10% HCl; the molar ratio of the compound (1) to the tin reagent is 1:3; the molar ratio of the n-butyl lithium to the compound (1) is 1:3.5;

[0015] Furthermore, the reflux reaction time in step 3 is preferably 9 hours; the molar ratio of the compound (2) to 5"-bromo-3',3"-dihexyl-[2,2':5',2"-terthiophene]-5-carboxaldehyde is 1:15; the molar ratio of the catalyst to the compound 3 is 20 mg:8.69 mmol;

[0016] Furthermore, the base in step 4 is piperidine; the reaction time of the Knoevenagel condensation reaction is 24 hours; the molar ratio of the 3-hexylrhodanine to the compound (4) is 15:1; and the molar ratio of the base to the compound (4) is 1.5 mL:0.592 mmol.

[0017] The invention discloses an application of an asymmetric donor material containing tin atoms in the preparation of organic photoelectric devices.

[0018] Furthermore, the organic photoelectric device can be used to prepare solar cells, organic light emitting diodes (OLEDs), and flexible displays.

[0019] The beneficial effects of the present invention are as follows: the tin atom-containing small molecule donor designed by the present invention can form an appropriate energy level difference with the acceptor material L8-BO, which is conducive to exciton dissociation and has better photovoltaic performance in the test of organic solar cells. The content of the tin element is properly controlled during synthesis according to actual conditions to ensure the improvement of material performance, while ensuring its synthetic feasibility and economy with good intermolecular stacking effect, which is conducive to the improvement of charge mobility.

[0020] In organic optoelectronic materials, by adjusting the structure of tin (Sn) compounds, the HOMO (highest occupied molecular orbital) and LUMO (lowest unoccupied molecular orbital) energy levels of the material can be effectively controlled to optimize the photovoltaic efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Compound 1 prepared by the present invention 1 H NMR spectrum (deuterated chloroform, 400 MHz).

[0022] Figure 2 Compound 2 prepared by the present invention 1 H NMR spectrum (deuterated chloroform, 400 MHz).

[0023] Figure 3 Compound 3 prepared by the present invention1 H NMR spectrum (deuterated chloroform, 400 MHz).

[0024] Figure 4 The compound Z2-Sn prepared in Example 1 of the present invention 1 H NMR spectrum (deuterated chloroform, 400 MHz).

[0025] Figure 5 The compound Z2-Sn prepared in Example 1 of the present invention 13 C NMR spectrum (deuterated chloroform, 400 MHz).

[0026] Figure 6 The compound Z2-Sn prepared in Example 1 of the present invention was blended with L8-BO in a mass ratio of 1.2:1 to prepare an organic photovoltaic device, and PM6:L8-Bo was blended in a mass ratio of 1.2:1 to prepare an organic photovoltaic device. The JV curves were measured under 1 simulated sunlight.

[0027] Figure 7 The electrochemical cyclic voltammetry curve of the organic photovoltaic device prepared by mixing the compound Z2-Sn prepared in Example 1 of the present invention with L8-BO in a mass ratio of 1.2:1.

[0028] Figure 8 The UV-visible absorption spectra of the solution and the film in Example 1 of the present invention were recorded using a Hitachi U-4100 spectrophotometer. DETAILED DESCRIPTION

[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] In the following examples, unless otherwise specified, the "water" used is deionized water.

[0031] Example 1: Synthesis of compound Z2-Sn,

[0032]

[0033] Synthesis of compound 1:

[0034] 1-Bromo-3-chloro-5-fluorobenzene (47.38 mmol) and magnesium powder (56.87 mmol) were added to a round-bottom flask filled with redistilled tetrahydrofuran (50 mL). Subsequently, iodine (20 mg) was added to the round-bottom flask as an initiator. The mixture was refluxed at 70 ° C for 4 h until the magnesium was completely consumed. After the reaction was naturally cooled to room temperature (25 ° C, the same below), Grignard reagent 1 was obtained. The newly prepared Grignard reagent 1 was then transferred to a dropping funnel and slowly dripped (30 drops per minute) into a toluene solution of 150 mL of benzo[1,2-b:4,5-b′]dithiophene-4,8-dione (118.45 mmol). Subsequently, 5-bromo-3-chloro-2-(2-hexyldecyl)thiophene (23.69 mmol) and magnesium powder (28.43 mmol) were added to a round-bottom flask filled with redistilled tetrahydrofuran (50 mL). Subsequently, iodine (20 mg) was added to the round-bottom flask as an initiator. The mixture was refluxed at 70°C for 2 h until magnesium was completely consumed. After the reaction was naturally cooled to room temperature (25°C, the same below), Grignard reagent 2 was obtained, and then the newly prepared Grignard reagent 2 was transferred to a dropping funnel and slowly dripped into the above mixed solution (30 drops per minute). Subsequently, the mixture was stirred at room temperature overnight, and then dihydrated tin chloride (II) (710.7 mmol) dissolved in 10% HCl (15 mL) was added, and the resulting solution was stirred at 50°C for 3 hours. After completion, the reaction mixture was naturally cooled to room temperature and poured into water. The resulting organic matter was extracted three times with dichloromethane and then dried over anhydrous sodium sulfate. After the solvent was removed by a rotary evaporator, the crude product was purified by silica gel column chromatography (eluent: petroleum ether) to obtain a pale white solid - Compound 1 (yield 63%), i.e. 4-(4-chloro-5-(2-hexyldecyl)thiophen-2-yl)-8-(3-chloro-5-fluorophenyl)benzo[1,2-b:4,5-b']dithiophene, which 1 H NMR spectrum is shown in Figure 1 .

[0035] Synthesis of compound 2

[0036] Under argon protection and at -78°C, n-butyl lithium (53.17 mmol, 1.6 M) was added dropwise (30 drops per minute) to a tetrahydrofuran solution (60 mL) of compound 1 (15.19 mmol). After the addition, the mixture was stirred at -78°C for 1 h. Then a tetrahydrofuran solution of trimethyltin chloride (45.57 mmol, 1 M) was added and stirred again at -78°C for 1 h, and then the mixture was naturally warmed to room temperature. After stirring at room temperature for 12 h, the solution was poured into deionized water, extracted three times with anhydrous ether (50 mL each time), and then dried over anhydrous sodium sulfate. After removing the solvent with a rotary evaporator, the crude product was recrystallized in toluene (the operating steps of recrystallization are: add 50 ml of toluene to the crude product, heat to 55-60°C to dissolve the product, turn off the heating after dissolution, cool naturally to room temperature, and leave for 5 hours, filter the precipitated crystalline product, the same below) twice to obtain a yellow solid compound 2 (the yield of this step is 80%). 1 HNMR Figure 2 .

[0037] Synthesis of compound 3

[0038] Under argon protection, compound 2 (8.69 mmol), 5"-bromo-3',3"-dihexyl-[2,2':5',2"-trithiophene]-5-carboxaldehyde (130.43 mmol) and tetrakis(triphenylphosphine)palladium (20 mg) were added to a round-bottom flask, and then anhydrous toluene (30 mL) was added thereto, and the mixture was stirred at 110°C for 9 h. After naturally cooling to room temperature, it was quenched with deionized water, and the resulting organic matter was extracted with dichloromethane 3 times (50 mL each time), and then dried with anhydrous sodium sulfate. After removing the solvent with a rotary evaporator, the crude product was purified by silica gel column chromatography (eluent: dichloromethane) to obtain a red solid compound 3 (the yield of this step is 48%), which 1 H NMR spectrum is shown in Figure 3 .

[0039] Synthesis of Compound Z2-Sn

[0040] Under argon protection, compound 4 (0.592mmol), 3-hexylrhodanine (8.88mmol) and 0.1mL piperidine were dissolved in dry chloroform (15mL). The mixed solution was stirred at 60°C for 24h, cooled to room temperature naturally, quenched with deionized water, extracted three times with chloroform (50mL each time), and the solvent was removed by rotary evaporator. The crude product was purified by column chromatography on silica gel (eluent was petroleum ether and chloroform in a volume ratio of 1:1) to obtain a red solid compound Z2-Sn (yield of this step 65%), i.e., the desired organic small molecule donor material compound Z2-Sn containing two fluorine atoms. 1 H NMR spectrum is shown in Figure 4 , 13 C NMR Figure 5 .

[0041] Example 2: Characterization of all-small molecule organic solar cell devices,

[0042] The organic photovoltaic device was prepared using the compound Z2-Sn prepared in Example 1 as a donor material and an acceptor material L8-BO, and the specific steps were as follows:

[0043] (1) After ultrasonic cleaning, ITO glass (indium tin oxide conductive glass) was treated with oxygen-plasma. PEDOT:PSS poly(3,4-ethylenedioxythiophene):poly(styrene sulfonic acid) (ratio 1:1, prepared as a mixed solution at the time of purchase) was first spin-coated on the ITO at 5000 rpm and annealed at 150°C for 15 minutes to obtain a substrate with a surface film thickness of about 40 nm.

[0044] (2) Then, the small molecule compound Z2-Sn prepared in Example 1 was used as a donor material and mixed with an acceptor L8-BO (the structural formula is shown below), and a mixed solvent of diiodomethane-chloroform (the volume ratio of diiodomethane to chloroform was 0.3 μL:100 μL) was added to prepare a blended solution (the total concentration of the donor and the acceptor was 20 mg / mL, and the mass ratio of the donor and the acceptor was 1.2:1). The blended solution was coated on the substrate in step (1) at a spin coating speed of 2000 rpm, and an active layer with a thickness of about 130 nm was coated on the surface of the substrate.

[0045] (3) The substrate obtained in step (2) was placed in a 60 nm culture dish, and then 60 μL of chlorobenzene was evenly applied on its surface, followed by solvent vapor annealing (85° C., 5 min). Next, an electron transport layer PNDIT-F3N thin film was coated on the active layer at a spin coating speed of 3000 rpm, with a film thickness of about 10 nm. Finally, a 100 nm thick silver layer was deposited on the electron transport layer by evaporation.

[0046] The specific performance parameters of solar cells are shown in Table 1 and Figure 6-7 shown.

[0047] (The equipment used in the laboratory of the present invention is a solar simulator, which is calibrated with a silicon solar cell, and all tests are measured under 1 simulated sunlight, 100mW / cm2).

[0048]

[0049]

[0050] Table 1 Photoelectric conversion efficiency of all-small molecule photovoltaic devices

[0051] Donor <![CDATA[V oc (V)]]> <![CDATA[J sc (mA / cm 2 )]]> FF(%) PCE(%) PM6:L8-Bo 0.87 24.80 73.08 16.13 Z2-Sn:L8-Bo 0.88 25.25 75.94 16.93

[0052] From the data in Table 1 and Figure 6 From the JV curve, we can see that compared with PM6:L8-Bo, the PCE (energy conversion efficiency) of PM6:Z2-Sn:L8-Bo has been significantly improved, and the FF (fill factor) has increased from 73.08% to 75.94%. sc (Current density) from 24.80mA / cm 2 Increased to 25.25mA / cm 2 This is because the blend of compounds Z2-Sn and L8-BO has a larger exciton diffusion coefficient and a faster exciton dissociation process than the blend based on compounds PM6 and L8-BO.

[0053] This type of small molecule has a clear molecular structure in all-small molecule organic solar cells, and the differences between materials and device batches are small, so it has unique advantages in commercialization. It is of great significance for us to build a high-efficiency organic solar cell system.

[0054] from Figure 7 It can be calculated that the HOMO energy level of the compound Z2-Sn is -5.04eV, and its LUMO energy level is -2.77eV, which can form an appropriate energy level difference with L8-BO, which is beneficial to exciton dissociation and improves the photoelectric conversion efficiency of photovoltaic devices.

[0055] from Figure 8 UV-Visible spectroscopy test chart: The UV-Vis absorption spectra of solutions and films were recorded using a Hitachi U-4100 spectrophotometer. The solution absorption test sample was dissolved in chloroform at a concentration of 0.01 mg / mL and measured at room temperature. The optical absorption spectrum of the film was prepared by spin coating a chloroform solution (5.0 mg / mL, 1500 rpm) onto a quartz plate. Figure 8 It can be seen that compound Z2-Sn has good intermolecular stacking effect, which helps to improve the charge mobility.

[0056] This application achieves a photoelectric conversion efficiency of 16.93% by introducing benzene rings and thiophene into small molecule donor materials at the same time, and introducing tin elements on the two-dimensional side chains to design and synthesize new small molecule donor materials. It has important application prospects in binary all-small molecule organic solar cells.

[0057] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

Claims

1. An asymmetric donor material containing tin atoms, characterized in that: Its structural formula is shown in Formula 1. In the structural formula, -X is a fluorine atom or a chlorine atom.

2. The method for preparing the asymmetric donor material containing tin atoms according to claim 1, characterized in that: The specific steps are as follows: Step 1: Using tetrahydrofuran as solvent and iodine as initiator, magnesium powder and 4-bromo-1,2-difluorobenzene are added, and the mixture is refluxed at 70°C for 4h until the magnesium is completely consumed, and naturally cooled to room temperature to obtain Grignard reagent 1, and Grignard reagent 1 is added dropwise to a toluene solution of benzo[1,2-b:4,5-b']dithiophene-4,8-dione, and stirred at room temperature. At the same time, using tetrahydrofuran as solvent and iodine as initiator, magnesium powder and 5-bromo-3-chloro-2-(2-hexyldiethyl)thiocin are added, and the mixture is Reflux at 70°C for 2h until magnesium is completely consumed, and cool naturally to room temperature to obtain Grignard reagent 2, then transfer the newly prepared Grignard reagent 2 to a dropping funnel and slowly drip into the mixed solution to which Grignard reagent 1 is added, then stir the mixture at room temperature overnight, then add tin (II) chloride dihydrate dissolved in 10% HCl at room temperature, and then continue to stir the resulting solution at 50°C for 3h. After the reaction is completed, cool naturally to room temperature and pour the reactant into water, i.e., compound (1); Step 2: under the protection of argon, n-butyl lithium solution is added dropwise to a tetrahydrofuran solution containing compound (1) at -78°C. After the addition is complete, the mixture is stirred at -78°C for 1 hour, and then compound (1) is added. The mixture is stirred at -78°C for 1 hour, and the temperature is naturally raised to room temperature for reaction for 12 hours. Subsequently, the mixture is cooled to room temperature, a tin reagent solution is added, and then the mixture is stirred at 50°C for another 3 hours to generate compound (2); Step 3: Under argon protection, using tetrakis(triphenylphosphine)palladium as a catalyst and toluene as a solvent, the compound (2) obtained in step 2 and 5"-bromo-3',3"-dihexyl -[2,2':5',2"-terthiophene]-5-carboxaldehyde is refluxed at 110°C for 8-10h to undergo Stille coupling reaction to obtain compound (3); Step 4: Under argon protection, compound (3), 3-hexylrhodanine and a base are added to chloroform solvent, and Knoevenagel condensation reaction is carried out at 60° C. to connect the rhodanine end groups to obtain an organic small molecule donor material containing an asymmetric two-dimensional side chain.

3. The method for preparing the asymmetric donor material containing tin atoms according to claim 2, characterized in that: In the step 1, the molar ratio of 5-bromo-3-chloro-2-(2-hexyldiethyl) thiocine, 4-bromo-1,2-difluorobenzene and benzo[1,2-b:4,5-b']dithiophene-4,8-dione is 1:2:5; and the molar ratio of benzo[1,2-b:4,5-b']dithiophene-4,8-dione to the tin reagent is 1:

5.

4. The method for preparing an asymmetric donor material containing tin atoms according to claim 2, characterized in that: The tin reagent solution in step 2 is prepared by dissolving tin (II) chloride dihydrate in 10% HCl; the molar ratio of the compound (1) to the tin reagent is 1:3; and the molar ratio of the n-butyl lithium to the compound (1) is 1:3.

5.

5. The method for preparing the asymmetric donor material containing tin atoms according to claim 2, characterized in that: The reflux reaction time in step 3 is preferably 9 hours; the molar ratio of the compound (2) to 5"-bromo-3',3"-dihexyl-[2,2':5',2"-terthiophene]-5-carbaldehyde is 1:15; and the molar ratio of the catalyst to the compound 3 is 20 mg:8.69 mmol.

6. The method for preparing an asymmetric donor material containing tin atoms according to claim 2, characterized in that: The base in step 4 is piperidine; the reaction time of the Knoevenagel condensation reaction is 24 hours; the molar ratio of the 3-hexylrhodanine to the compound (4) is 15:1; and the molar ratio of the base to the compound (4) is 1.5 mL:0.592 mmol.

7. Use of the asymmetric donor material containing tin atoms according to claim 1 in the preparation of an organic optoelectronic device.

8. Use of the asymmetric donor material containing tin atoms according to claim 7 in the preparation of an organic optoelectronic device; characterized in that: The organic photoelectric device can be applied to the preparation of solar cells, organic light emitting diodes (OLEDs), and flexible displays.

Citation Information

Cited By

  • Fully asymmetric small molecule donor SMD-Aey and preparation method and application thereof

    CN121673295A